Toxic Effect of Cadmium on the Electrophoretic Protein Patterns of Gill and Muscle of Oreochromis mossambicus - K. Muthukumaravel; P. Kumarasamy; A. Amsath; M. Gabriel Paulraj (E-Journal of Chemistry)
The present study was carried out to determine the sub lethal toxic effects of the heavy metal cadmium on the electrophoretic protein fractions of gill and muscle tissues of Oreochromis mossambicus. Fishes were exposed to 10% sub lethal concentration (96 h LC50) of cadmium for a period of 10 days. The protein fractions in the muscle of experimental fishes were found to be increased (twelve fractions) with respect to controls (eight fractions). The numbers of protein fractions in the gills of test fishes were found to be lesser than the control fishes. The results of the present study prove that cadmium affects the protein fractions in the tissues of fishes.